2001
DOI: 10.1016/s0378-4371(01)00439-3
|View full text |Cite
|
Sign up to set email alerts
|

Statistical mechanics and capacity-approaching error-correcting codes

Abstract: I will show that there is a deep relation between error-correction codes and certain mathematical models of spin glasses. In particular minimum error probability decoding is equivalent to finding the ground state of the corresponding spin system. The most probable value of a symbol is related to the magnetization at a different temperature. Convolutional codes correspond to one-dimensional spin systems and Viterbi's decoding algorithm to the transfer matrix algorithm of Statistical Mechanics.I will also show h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…and therefore lim j→∞ inf σ ∈K c j x≥L J (σ, x) = +∞ for every L. This is condition (11). As to (12), for bounded continuous functions g we have…”
Section: Lemma 27mentioning
confidence: 87%
See 1 more Smart Citation
“…and therefore lim j→∞ inf σ ∈K c j x≥L J (σ, x) = +∞ for every L. This is condition (11). As to (12), for bounded continuous functions g we have…”
Section: Lemma 27mentioning
confidence: 87%
“…Then the condition (10) is verified. Therefore, if (11) is also verified, the tail condition (6) holds true.…”
Section: Theorem 11mentioning
confidence: 93%
“…In analogy to classical (commutative) probability theory, all cumulants of the limit distribution P C∞ (x) except for mean and variance vanish. Therefore, the classical central limit theorem can easily be proven along the same lines as (141) and (144). The limit distribution is called the normal distribution, in general, and Gaussian and semicircle distribution for commutative and non-commutative random variables, respectively.…”
Section: Free Central Limit Theoremmentioning
confidence: 98%
“…For further results, the reader is referred to, e.g. [144,145]. The replica method is not the only tool from statistical physics that is applied for the analysis of error correction codes.…”
Section: Th Example: Low-density Parity Check Codesmentioning
confidence: 99%
“…The connection between error-correcting transmission codes and spin systems was recognized by N. Sourlas [25,26,27]. In particular, it was shown that the usual binary parity checks b 1 ⊕ b 2 ⊕ .…”
Section: Discussionmentioning
confidence: 99%